2021
DOI: 10.1136/bcr-2020-240368
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cannula used for continuous intraoral mandibular nerve block in trigeminal neuralgia

Abstract: Trigeminal neuralgia is a chronic pain condition affecting one or more distributions of the trigeminal nerve. Patients with this condition experience short, sharp, shooting pain attacks, which can progress to longer, more frequent durations. The pain is often difficult to control. We report of a man who was admitted with severe neuralgia of the third division of the trigeminal nerve. Talking and any oral intake triggered a severe agonising pain. The latter made the regular oral intake of analgesia challenging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Sawhney et al [ 9 ] reported that an intermittent mandibular nerve block via the lateral extraoral approach was effective for pain relief after surgery for a mandibular parasymphyseal fracture. A continuous mandibular nerve block is effective for the relief of pain caused by MRONJ [ 8 ], mandibular fracture [ 10 ], and trigeminal neuralgia [ 11 ]. Dziadzko et al [ 12 ] reported that a continuous bilateral nerve block was effective for painful trismus in patients with tetraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Sawhney et al [ 9 ] reported that an intermittent mandibular nerve block via the lateral extraoral approach was effective for pain relief after surgery for a mandibular parasymphyseal fracture. A continuous mandibular nerve block is effective for the relief of pain caused by MRONJ [ 8 ], mandibular fracture [ 10 ], and trigeminal neuralgia [ 11 ]. Dziadzko et al [ 12 ] reported that a continuous bilateral nerve block was effective for painful trismus in patients with tetraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…However, Aquilanti et al highlighted the rare but potential nerverelated adverse effects of inferior alveolar nerve block anesthesia, emphasizing the need for a balanced discussion with patients (16). Stringer et al reported a case where continuous intraoral mandibular nerve block provided effective pain relief in a patient with trigeminal neuralgia(17).…”
mentioning
confidence: 99%